PUBLIC INFRASRUCTURE PROJECT FAILURES IN NIGERIA: CAUSES AND CONSEQUENTIAL EFFECTS ON ECONOMY AND WELFARE OF CITIZENRY - YUSUF GARBA MANJO (International Studies Journal)
Nigerian state particularly at national and sub-national levels, have experienced public infrastructure project failures during execution of their projects, though, there may be some differences among the level of failures, causes, and effects of such failures at federal, state and local government levels. The aim of this study is to examine and investigate the reasons behind the failure of public infrastructure projects in Nigeria. In practical terms, the implementation of public infrastructure projects in Nigeria has encountered several challenges, which usually results into failures of some projects. The investigation in to the failure of infrastructure project was conducted through qualitative methods. Data were obtained from secondary sources, such as books, journals, archival documents, newspapers, magazines, and websites that host related data on public infrastructure projects. The data were further examined using a content analysis technique.  The study found that the failures of public infrastructure projects is a recurring decimal in Nigeria, due to variety of causes such as poor financial capability, inaccurate costing, corruption, incompetence, poor planning and estimation, poor contracting and contractor practices, poor communication, frequent scope changes and design errors, poor leadership, interference from socio-cultural and political factors. The adverse effects of these failures on the economy and citizen’s welfare is colossal  as it involves loss of state revenue, citizen revenue losses, project cost overruns, low community empowerment, slow economic growth, underdevelopment of infrastructure sector, a loss of foreign aid and grants, stricter donor regulations, the loss of elections by the incumbent leadership at state and federal levels, and a lack of trust in government by financial institutions to further finance public infrastructure projects. Based on this, study recommends that government agencies in charge of overseeing and monitoring public infrastructure projects such as the National Council on Public Procurement, Bureau of Public Procurement, and Due Process Office should be re-organized and reformed to carry out their statutory responsibilities efficiently and effectively without adopting unethical methods.  These findings and recommendations are the contributions of this work to scholarship as they are different from the previous related studies.